NutriCare: Aplikasi Pemantau Gizi Ibu Hamil untuk Menghindari Stunting dengan Memenuhi Kebutuhan Kalori dan Zat Besi - Maharani, Tarisyah Puan; Budhisantoso, Nugroho (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2025)
Stunting in children under five, due to chronic malnutrition since in the womb, has an impact onchildren's health and cognitive development as well as the potential for long-term economic losses.In Indonesia, the prevalence of stunting will reach 21.6% in 2022. Iron and calorie deficiency inpregnant women is the main factor causing stunting, with 48.6% of pregnant women experiencinganemia. Many pregnant women lack easily accessible nutritional information. The Hilda AlnairaClinic in Koja, North Jakarta, faces challenges in providing manual nutritional recommendationsthat are inefficient and lack personalization. This research aims to develop the "NutriCare" mobileapplication to help pregnant women monitor calorie and iron intake. This Android-basedapplication was developed using a prototypemethod, easy-to-use interface, relevant features, testedusing the black box method, and optimized before full implementation. This application helpsincrease pregnant women's understanding of nutrition and supports maternal health and fetaldevelopment in efforts to prevent stunting.